Pulmonary NUT carcinoma, an elusive and refractory entity, shows transient response to chemotherapeutics and PD-1 inhibitor: a case report and literature review - Yang, Guangjian; Liu, Runze; Yang, Linke; Yang, Xue; Tang, Xiaoyong; Mao, Huiqing (Frontiers in Immunology, 2025)
Nuclear protein of the testis (NUT) carcinoma (NC) is a rare but highly aggressive disease, characterized by drug resistance and poor prognosis. This report describes the case of a 32-year-old male patient diagnosed to have pulmonary NC; the tumor exhibited positive immunohistochemical staining of NUT and showed rearrangement of BRD4::NUT midline carcinoma family member 1 (NUTM1). After two treatment cycles of chemotherapy (etoposide plus carboplatin) combined with the PD-1 inhibitor sintilimab, the thoracic lesion of the patient disappeared, resulting in a partial response. When the patient’s disease progressed even after the targeted therapy with a bromodomain and extra-terminal motif (BET) inhibitor, sintilimab was readministered in combination with platinum-based chemotherapy. However, the disease rapidly progressed after only one treatment cycle. Notably, the disease showed de novo drug resistance to the combination of chemotherapy with the histone deacetylase inhibitor. Although the patient’s NC initially responded well to the combination of the PD-1 inhibitor and chemotherapy, the response was transient. These findings suggest that pulmonary NC is a highly malignant thoracic carcinoma, with no durable response and survival benefits from treatment with chemotherapeutics or immune checkpoint inhibitors.